Meiotic drive reduces egg-to-adult viability in stalk-eyed flies. Issue 1910 (4th September 2019) - Finnegan, Sam Ronan; White, Nathan Joseph; Koh, Dixon; Camus, M. Florencia; Fowler, Kevin; Pomiankowski, Andrew
Abstract : A number of species are affected by Sex-Ratio (SR) meiotic drive, a selfish genetic element located on the X-chromosome that causes dysfunction of Y-bearing sperm. SR is transmitted to up to 100% of offspring, causing extreme sex ratio bias. SR in several species is found in a stable polymorphism at a moderate frequency, suggesting there must be strong frequency-dependent selection resisting its spread. We investigate the effect of SR on female and male egg-to-adult viability in the Malaysian stalk-eyed fly, Teleopsis dalmanni . SR meiotic drive in this species is old, and appears to be broadly stable at a moderate (approx. 20%) frequency. We use large-scale controlled crosses to estimate the strength of selection acting against SR in female and male carriers. We find that SR reduces the egg-to-adult viability of both sexes. In females, homozygous females experience greater reduction in viability ( s f = 0.242) and the deleterious effects of SR are additive ( h = 0.511). The male deficit in viability ( s m = 0.214) is not different from that in homozygous females. The evidence does not support the expectation that deleterious side effects of SR are recessive or sex-limited. We discuss how these reductions in egg-to-adult survival, as well as other forms of selection acting on SR, may maintain the SR polymorphism in this species.